The complete chloroplast genome of Catalpa ovata (Bignoniaceae): an important ornamental and medicinal plant. Issue 2 (2nd April 2020) - Wang, Yan; Zhao, Yue; Wang, Kuan; Wang, Lei; Feng, Yan; Qi, Lipan; Luo, Yating; Ji, Yihong; Gong, Xuechen
Abstract: Catalpa ovata is an ornamental tree species belonging to the Bignoniaceae family and also a valuable wood production plant. In this study, we sequenced the complete chloroplast genome of C . ovata and discussed its phylogenetic relationship. The complete chloroplast genome of C. ovata is 158, 279 bp in size, comprising of a large single-copy (LSC, 85, 004 bp) and a small single-copy (SSC, 12, 675 bp) regions, separated by two inverted repeat regions (IRs, 30, 300 bp each). The total GC content was 38.1%. The chloroplast genome contains 131 genes, including 86 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis showed that the complete chloroplast genome sequence of C. ovata can be used as a super DNA barcoding to distinguish it from other plants. This study will provide genetic resources for species identification of C. ovata .